2010
DOI: 10.1007/jhep09(2010)065
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic MSSM on a resolved orbifold

Abstract: We construct an MSSM with three generations from the heterotic string compactified on a smooth 6D internal manifold using Abelian gauge fluxes only. The compactification space is obtained as a resolution of the T 6 / 2 × 2 × 2,free orbifold. The 2,free involution of such a resolution breaks the SU(5) GUT group down to the SM gauge group using a suitably chosen (freely acting) Wilson line. Surprisingly, the spectrum on a given resolution is larger than the one on the corresponding orbifold taking into account t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 58 publications
1
99
0
1
Order By: Relevance
“…Anderson et al (2010), but is chosen for phenomenological reasons, and hence this does not answer the question why nature would have chosen this option. Also in the heterotic mini-landscape an example was found (Blaszczyk et al, 2010), but only after numerous examples with massless, vector-like fractional charges. But these authors suggested another rationale for using freely acting symmetries, namely that otherwise the Standard Model Y charge breaks if the orbifold singularities are "blown up".…”
Section: Grand Unification In String Theorymentioning
confidence: 99%
“…Anderson et al (2010), but is chosen for phenomenological reasons, and hence this does not answer the question why nature would have chosen this option. Also in the heterotic mini-landscape an example was found (Blaszczyk et al, 2010), but only after numerous examples with massless, vector-like fractional charges. But these authors suggested another rationale for using freely acting symmetries, namely that otherwise the Standard Model Y charge breaks if the orbifold singularities are "blown up".…”
Section: Grand Unification In String Theorymentioning
confidence: 99%
“…Only a relatively small number of models exhibiting a realistic massless spectrum have been constructed in this way, some with [6] and some without [5,11,18] antibranes, reflecting the considerable technical problems associated with vector bundles on smooth Calabi-Yau manifolds. They are complemented by models found in related heterotic constructions such as those based on orbifolds [19][20][21][22][23][24][25][26][27][28], on the free fermionic strings [29][30][31], and on Gepner models [32][33][34].…”
Section: Jhep06(2012)113 1 Introductionmentioning
confidence: 99%
“…Since the multiplicity operator (22) is insensitive to fully vector-like states, we calculate their spectrum via equivariant line bundle cohomology. 2 For this we use the automated computer tool cohomcalg [61,62]. Starting from those models that are chiral exact, we compute the full spectrum to see whether they have at least one non-chiral 5-5 pair.…”
Section: Analysis Beyond the Chiral Spectrummentioning
confidence: 99%
“…Even though all three of them were roughly discovered around the same time, essentially only the E 8 ×E 8 theory has been examined in string model building on Calabi-Yau manifolds in a more systematic fashion. On smooth compact orbifold resolutions semirealistic models were obtained from the E 8 ×E 8 theory using line bundles [1][2][3]. In the class of favorable Complete Intersection Calabi-Yaus (CICYs) with discrete symmetries, specific S(U(1) 5 ) line bundle constructions embedded in a single E 8 factor have been investigated in [4][5][6].…”
Section: Introductionmentioning
confidence: 99%